Elevated Proportions of Deleterious Genetic Variation in Domestic Animals and Plants. (9th January 2018) - Makino, Takashi; Rubin, Carl-Johan; Carneiro, Miguel; Axelsson, Erik; Andersson, Leif; Webster, Matthew T
Abstract: A fraction of genetic variants segregating in any population are deleterious, which negatively impacts individual fitness. The domestication of animals and plants is associated with population bottlenecks and artificial selection, which are predicted to increase the proportion of deleterious variants. However, the extent to which this is a general feature of domestic species is unclear. Here, we examine the effects of domestication on the prevalence of deleterious variation using pooled whole-genome resequencing data from five domestic animal species (dog, pig, rabbit, chicken, and silkworm) and two domestic plant species (rice and soybean) compared with their wild ancestors. We find significantly reduced genetic variation and increased proportion of nonsynonymous amino acid changes in all but one of the domestic species. These differences are observable across a range of allele frequencies, both common and rare. We find proportionally more single nucleotide polymorphisms in highly conserved elements in domestic species and a tendency for domestic species to harbor a higher proportion of changes classified as damaging. Our findings most likely reflect an increased incidence of deleterious variants in domestic species, which is most likely attributable to population bottlenecks that lead to a reduction in the efficacy of selection. An exception to this pattern is displayed by European domestic pigs, which do not show traces of a strong population bottleneck and probably continued to exchange genes with wild boar populations after domestication. The results presented here indicate that an elevated proportion of deleterious variants is a common, but not ubiquitous, feature of domestic species.